Adjuvant systemic therapy after resection of node positive gallbladder cancer: Time for a well-designed trial? (Results of a US-national retrospective cohort study). (April 2018) - Bergquist, John R.; Shah, Harsh N.; Habermann, Elizabeth B.; Hernandez, Matthew C.; Ivanics, Tommy; Kendrick, Michael L.; Smoot, Rory L.; Nagorney, David M.; Borad, Mitesh J.; McWilliams, Robert R.; Truty, Mark J.
Abstract: Background: Ideal oncologic management of gallbladder carcinoma (GBCA) after complete surgical resection is unclear. We sought to define benefit of post-resection adjuvant systemic chemotherapy alone in T2 or greater gallbladder carcinoma utilising a large national dataset. Study Design: The National Cancer Data Base (NCDB) 2004–2012 cohort was retrospectively reviewed for patients with GBCA (T2+) undergoing curative-intent resection and surviving at least 6 weeks. Univariate group comparisons, unadjusted Kaplan-Meier and adjusted Cox proportional hazards analyzed overall survival. Results: 4373 patients were included (N = 2479 T2, N = 1894 T3/4). Overall, 22.1% of patients received adjuvant chemotherapy. Use of multi-agent chemotherapy increased during the study period. Patients receiving adjuvant therapy were younger, had fewer comorbidities, more often node-positive and more likely R1-margins than those receiving surgery alone. Unadjusted overall survival was improved in all patients with node-positive disease as well as for those with inadequate nodal staging. The benefit of chemotherapy persisted after adjustment for patient and tumor factors. Conclusion: Adjuvant systemic chemotherapy is associated with survival benefit in patients with T2 or greater GBCA with node positive disease. We recommend a multidisciplinary approach in these patients as less than 1-in-4 of them currently receive adjuvant chemotherapy. Future clinical trials should address adjuvant chemotherapy in node positive GBCA. Highlights: Patients with T2 or greater GBCA node positive disease derive survival benefit from post-resection adjuvant chemotherapy. We recommend multidisciplinary approach in these patients as only 25% of them currently receive adjuvant chemotherapy. Future clinical trials should address adjuvant chemotherapy in node positive GBCA.